The Benefits of Pop Up Book Media in Implementing Joyful Learning as an Effort to Improve Understanding of Fiqih Among Students of Madrasah Ibtidaiyah - Zakiyah BZ; Nur Ainin Sofiyah Zanjabela (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2026)
Fiqh learning in Madrasah Ibtidaiyah is often considered difficult and boring by students because the material is abstract and requires practical understanding. Therefore, a fun and easy-to-understand learning method is needed. This study aims to describe the application of joyful learning using pop-up book media in improving students' understanding of fiqh on ablution material in class II of Madrasah Ibtidaiyah Raudatul Jannah Tiris Probolinggo. This study is a descriptive qualitative study conducted with data collection techniques through observation, interviews, and documentation. The results showed that the use of pop-up book media was able to create a more lively and enjoyable learning atmosphere. Students looked more enthusiastic, focused, and active during the learning process. The display of three-dimensional images in the pop-up book helped students understand the sequence and procedures of ablution more clearly and made it easier for them to practice. Therefore, the use of a joyful learning approach combined with pop-up book media was able to create a fun learning atmosphere and improve students' understanding of the material.